2021
DOI: 10.1038/s41598-021-03534-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of dyslipidemia, diabetes and metabolic syndrome with serum ferritin levels: a middle eastern population-based cross-sectional study

Abstract: Elevated serum ferritin (SFer) levels are implicated in many energy metabolism abnormalities. The association between SFer levels and metabolic disorders has not been studied in Middle Eastern populations. We aimed at exploring the association between SFer levels and serum lipids, diabetes determinants, and metabolic syndrome in a sample of Qatari adults. This study used biochemical parameters obtained from 1928 participants from the Qatar Biobank cohort. We utilized adjusted multivariable logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…Moreover, even though it did not reach statistical significance, probably because of the sample size, we found an increase in PLR in prediabetic subjects, and we found a significant increase in PLR in diabetic patients compared with controls; furthermore, this parameter was associated with HbA1c and HOMA-IR in the simple regression analysis. This observation is consistent with previous studies in different populations and suggests that prediabetes is a proinflammatory condition [ 46 , 47 ]. Our group previously explored this hypothesis, demonstrating an impaired inflammatory profile in subjects with early glucose intolerance status and metabolic syndrome [ 6 , 48 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, even though it did not reach statistical significance, probably because of the sample size, we found an increase in PLR in prediabetic subjects, and we found a significant increase in PLR in diabetic patients compared with controls; furthermore, this parameter was associated with HbA1c and HOMA-IR in the simple regression analysis. This observation is consistent with previous studies in different populations and suggests that prediabetes is a proinflammatory condition [ 46 , 47 ]. Our group previously explored this hypothesis, demonstrating an impaired inflammatory profile in subjects with early glucose intolerance status and metabolic syndrome [ 6 , 48 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study demonstrated a significant association in increased ferritin levels with higher lipid levels and the risk of dyslipidemia, independent of confounding factors, such as age, gender, and lifestyle factors, which is consistent with previous studies in several countries [ 12 , 22 , 23 ]. However, the mechanism driving the relationship of circulatory ferritin with lipid metabolism is not fully understood.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, it was observed that the patients with higher ferritin levels were suffered from more metabolism disorders that included dyslipidemia and hypertension. Several previous studies have indicated the similar results that increased ferritin levels are associated with disrupted lipid metabolism in T2DM ( 24 26 ). Higher serum iron levels, TSAT levels, and hs-CRP levels are found in the patients with the highest tertile of ferritin levels.…”
Section: Discussionsupporting
confidence: 69%